A comprehensive allometric analysis of 2nd digit length to 4th digit length in humans. Issue 1857 (28th June 2017) - Lolli, Lorenzo; Batterham, Alan M.; Kratochvíl, Lukáš; Flegr, Jaroslav; Weston, Kathryn L.; Atkinson, Greg
Abstract : It has been widely reported that men have a lower ratio of the 2nd and 4th human finger lengths (2D : 4D). Size-scaling ratios, however, have the seldom-appreciated potential for providing biased estimates. Using an information-theoretic approach, we compared 12 candidate models, with different assumptions and error structures, for scaling untransformed 2D to 4D lengths from 154 men and 262 women. In each hand, the two-parameter power function and the straight line with intercept models, both with normal, homoscedastic error, were superior to the other models and essentially equivalent to each other for normalizing 2D to 4D lengths. The conventional 2D : 4D ratio biased relative 2D length low for the generally bigger hands of men, and vice versa for women, thereby leading to an artefactual indication that mean relative 2D length is lower in men than women. Conversely, use of the more appropriate allometric or linear regression models revealed that mean relative 2D length was, in fact, greater in men than women. We conclude that 2D does not vary in direct proportion to 4D for both men and women, rendering the use of the simple 2D : 4D ratio inappropriate for size-scaling purposes and intergroup comparisons.